(untitled) (Research, Society and Development, 2020)
Semisolid drug development is a strategy applied for drug release, both local and systemically administration. However, as the skin has several layers, the formulation must be designed in order to overcome these barriers. As in 2019, Brazilian Health Surveillance National Agency (Anvisa) has published No. 20/2019 Guide, that disposes about Quality Requirements to Topical and Transdermal Products Register, which contains quality analysis and in vitro performance evaluation assays. No. 20/2019 Guide, although it is current, it is available for contributions throughout one year from its publication. Thus, it was led a bibliographical research about the available assays to quality evaluation of semisolid products produced on a generic drugs industry based on information mentioned on No. 20/2019 Guide. That was considered cream, oilment, and gel formulations and applied on indicated tests, such as release and permeation tests, forasmuch as the formulation characteristics, route of administration, and place of action. It was evaluated the apparatus mix applied and the peculiarities for the respective analysis as well. According to the results found, it is possible to affirm that both the assays are specific for the study of the three semisolid forms, regarding the “sameness” between the apparatus as the respectively values are similar.